Plasmon resonances of isolated metal wire and shell - Стогний, Н.П.; Бутенко, Н.С. (Radiotekhnika, 2020)
The surface and bulk plasmons of isolated metal wire and shell are investigated. The metal wire model was a circular cylinder of infinite length, the medium inside which was described by the Drude formula. The eigenstates of the field, existing in the absence of sources, and the vibrations excited by external fields are studied. Bulk plasmons in the metal transparency domain are considered. The main attention is paid to the study of surface plasmons existing in the metal opacity domain and only for H-polarized fields. Their complex eigenfrequencies, Q-factors and field distributions are investigated. Despite the fact that the dispersion equation for the isolated wire has a solution for an arbitrary number of angular field variations, it has been found that in the Scattering Cross Section (SCS) for an optically thin nanowire there is only one resonance peak corresponding to a dipole plasmon. With an increase in the radius of the wire the maximum of the SCS shifts toward multipole plasmons. With a decrease in absorption additional resonance peaks appear in the SCS of isolated wire. It is found that in contrast to isolated wire the dispersion equation has two different solutions for a nanoshell for each fixed number of angular variations in the field. There are plasmons whose magnetic field on the inner and outer sides of the shell has the same sign (even plasmons) or different signs (odd plasmons). The splitting of plasmon resonances is shown. The odd plasmons are shifted to the region of lower frequencies and the even plasmons are shifted to the region of higher frequencies compared to the plasmon resonances of wire. It was found that the splitting of the resonant frequencies increases with decreasing thickness of shell. In this case the width of the resonance peaks also decreases which indicates an increase in the Q-factor.